MeCP2 behaves as an elongated monomer that does not stably associate with the Sin3a chromatin remodeling complex. - Klose, R; Bird, A (2004)
MeCP2 is a transcription factor that recognizes and binds symmetrically methylated CpG dinucleotides to repress transcription. MeCP2 can associate with the Sin3a/histone deacetylase corepressor complex and mediate repression in a histone deacetylase-dependent manner. In extracts from rodent tissues, cultured cells, and Xenopus laevis oocytes, we find that only a small amount of mammalian MeCP2 interacts with Sin3a and that this interaction is not stable. Purification of rat brain MeCP2 (53 kDa) indicates no associated proteins despite an apparent molecular mass by size exclusion chromatography of 400-500 kDa. Biophysical analysis demonstrated that the large apparent size was not because of homo-multimerization, as MeCP2 consistently behaves as a monomeric protein that has an elongated shape. Our findings indicate the MeCP2 is not an obligate component of the Sin3a corepressor complex and may therefore engage a more diverse range of cofactors for repressive function.